Salazar the dictator who refused to die - Gallagher, Tom. (London Hurst & Company, 2022)
Fifty years after his death, Portugal's Salazar remains a controversial and enigmatic figure, whose conservative and authoritarian legacy still divides opinion. Some see him as a reactionary and oppressive figure who kept Portugal backward, while others praise his honesty, patriotism and dedication to duty. Contemporary radicals are wary of his unabashed elitism and skepticism about social progress, but many conservatives give credit to his persistent warnings about the threats to Western civilization from runaway materialism and endless experimentation.
Includes bibliographical references and index.
Keywords: Salazar, António de Oliveira, 1889-1970; Prime ministers -- Portugal -- Biography